Effects of impulse purchases and personal indebtedness on financial stress - Medeiros Alves de Oliveira, Carolina Helena; Holanda Nepomuceno Nobre, Liana; Chaves Nobre, Fábio (Retail Management Review, 2022)
Objective: Analyze the influence of impulse purchases and indebtedness on the level of the financial stress of students of the Administration course of a Federal University of Rio Grande do Norte. Methodology: A quantitative and explanatory study was carried out, with a cross-sectional cut. The sample consisted of 158 students and the collection was carried out in the university's own classrooms. The financial stress was measured using the InCharge Financial Stress/Financial Well-Being Scale, developed by Prawitz et al. (2006), and the existing relationships between the constructs were analyzed using multiple linear regression and discriminant analysis. Originality: The study contributes to the understanding of the effects of impulse purchases and financial indebtedness, as proxies for the absence of individual financial planning, on financial stress. Main results: The results reveal that students have a high level of financial stress, and, coherent with the literature, findings suggest that personal indebtedness positively affects financial stress. Impulse purchases, on the other hand, negatively affect financial stress. Theoretical Contributions: Financial stress, as opposed to financial well-being, is affected by both impulse purchases and indebtedness. The relation between indebtedness and financial stress corroborated the literature on the topic, however, impulse purchases act as a reducer of financial stress, a stress-reducing effect, suggesting that the psychological effect of this habit overcomes its negative financial effect.